Control strategy analysis of the hydraulic hybrid excavator. Issue 2 (February 2015) - Shen, Wei; Jiang, Jihai; Su, Xiaoyu; Reza Karimi, Hamid
Abstract Applying the electric hybrid technique on the off-road vehicle is one popular method to reduce the fuel consumption. However, the high cost, low energy conversion efficiency and disposal of used batteries are still the main problems. This paper is focusing on one alternative choice which is hydraulic hybrid off-road vehicles. Among the most typical off-road vehicles, the excavator is chosen as the prototype to study the control strategy. First, the basic principle of the hydraulic hybrid excavator based on Common Pressure Rail is introduced. Then, the mathematical model of the whole excavator is created. Moreover, the dynamic programming algorithm is used to solve the optimal control variable trajectory under a given circle. Finally, the adjustable single point under quasi constant pressure strategy is presented. The simulation result shows that the proposed strategy can reduce the fuel consumption clearly without deteriorating the performance.